Sistem Pengelolaan Sampah Di TPA Malimpung Kabupaten Pinrang - Rafidah, Rafidah; Masdayanti, Masdayanti; Haidah, Nur (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
A Waste Final Processing Site (TPA) is a location where all waste is collected safely so as not to cause disturbance to the environment. The condition and management of the malimpung landfill are not good. Lindih in the Malimpung landfill has a lot of seep and leachate water is only accommodated in ponds that are not treated properly so as not to pollute the environment. This study aims to determine the waste management system in Malimpung Landfill, Pinrang Regency. This study is observational by using a descriptive approach to determine the waste management system in Malimpung Landfill, Pinrang Regency. The results of this study show that the facilities and infrastructure in the Malimpung landfill are public facilities such as: entrance roads, guard offices/posts, drainage channels, fences, and signboards. Protection facilities such as; waterproof layer, leachate collection channels, gas vents, buffer areas and overburden. Supporting facilities such as: weighbridge and electricity. operational facilities such as heavy equipment There are 2 excavators and 1 bulldozer and there are 15 garbage transport trucks. And other facilities such as: leachate water treatment plants and monitoring wells. The average amount of waste generation that enters the landfill for 8 days is 76,125 tons / day. The resulting capacity of the Malimpung landfill is 586,000 m³. The landfill manager provides facilities and infrastructure in the form of clean water facilities so that officers do not use dirty water for purposes such as bathing and washing vehicles. Provide workshops and hangars to make it easier if garbage trucks or heavy equipment are damaged. Keywords: final processing site (TPA), facilities and infrastructure and capacity